2015
DOI: 10.1007/s12410-015-9344-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CT vs. Stress Testing in Patients with Suspected Coronary Artery Disease: Review and Expert Recommendations

Abstract: Diagnosis and management of coronary artery disease represent a major challenge to our health care systems affecting millions of patients each year. Until recently, the diagnosis of coronary artery disease could be conclusively determined only by invasive coronary angiography. To avoid risks from cardiac catheterization, many healthcare systems relied on stress testing as gatekeeper for coronary angiography. Advancements in cardiac computed tomography angiography technology now allows to noninvasively visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 93 publications
1
9
0
1
Order By: Relevance
“…20 Future investigations will define the role of coronary atheroma quantification for clinical management, particularly, in comparison to the many emerging tools available with cardiac CT, e.g, myocardial perfusion imaging, CT-FFR, or transluminal attenuation gradient assessment. 21 …”
Section: Discussionmentioning
confidence: 99%
“…20 Future investigations will define the role of coronary atheroma quantification for clinical management, particularly, in comparison to the many emerging tools available with cardiac CT, e.g, myocardial perfusion imaging, CT-FFR, or transluminal attenuation gradient assessment. 21 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Accumulating evidences have demonstrated that noninvasive CCTA was the preferred examination method of coronary artery disease (CAD). 1,2 Accumulating evidences have demonstrated that noninvasive CCTA was the preferred examination method of coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) has been wellknown as a noninvasive, strong security, and convenient technique providing visualized and reliable pathological results for clinical diagnosis. 1,2 Accumulating evidences have demonstrated that noninvasive CCTA was the preferred examination method of coronary artery disease (CAD). It had the advantage of high sensitivity and specificity as well as negative predictive value in comparison with invasive CCTA which was served as the standard of reference for the detection of CAD due to its high temporal resolution and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Эти данные вполне согласуются с результатами многоцентровых исследований [20,21], в которых отмечена лишь умеренная точность ОФЭКТ в выявлении ИБС -значения ROC-кривой были в пределах 0,67-0,69. У целого ряда исследователей [13,22] складывается впечатление, что это является общей проблемой для неинвазивных тестов по выявлению ишемии миокарда, которые уступают в диагностических возможностях МСКТ-ангиографии КА.…”
Section: Discussionunclassified